2018
DOI: 10.1002/hed.25327
|View full text |Cite
|
Sign up to set email alerts
|

Association between diffuse lymphocytic infiltration and papillary thyroid cancer aggressiveness according to the presence of thyroid peroxidase antibody and BRAFV600E mutation

Abstract: Although DLI was associated with multifocality regardless of TPOAb positivity, it was associated with an indolent feature when TPOAb was positive but with aggressive features in PTC with wild-type BRAF when TPOAb was negative. The TPOAb and BRAF status may help to define the clinical implication of lymphocytic infiltration found with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Therefore, if serological antibody analysis is not consistent with the pathological diagnosis, we prefer the latter. On the other hand, TPOAb positivity without diffuse lymphatic invasion is not related to tumor invasiveness 36. So, antibodies were not discussed and excluded as factors in this study of prognostic factors associated with PTC.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, if serological antibody analysis is not consistent with the pathological diagnosis, we prefer the latter. On the other hand, TPOAb positivity without diffuse lymphatic invasion is not related to tumor invasiveness 36. So, antibodies were not discussed and excluded as factors in this study of prognostic factors associated with PTC.…”
Section: Discussionmentioning
confidence: 94%
“…TPOAb are also found to be associated with the absence of distant metastases in patients with newly diagnosed breast cancer ( 33 ). Lee et al ( 17 ) suggested that diffuse lymphocytic infiltration was associated with aggressive features in PTC when TPOAb was negative, but tend to be indolent when TPOAb was positive. However, in the present study, both univariate and multivariate Logistic Regression analyses failed to identify the effect of TPOAb+ and/or TgAb+ status, or even extremely high levels of TPOAb or TgAb, on LNM of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that Hashimoto's thyroiditis (HT) is associated with increased risk of thyroid cancer (14)(15)(16). While the role of HT in LNM in patients with thyroid cancer remains conflicting (15,17,18). Although HT has been reported for not influencing the risk of recurrence in patients with PTC (19), there are also several studies demonstrated that HT is associated with less aggressiveness and tend to be a protective factor for LNM (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, thanks to the expansion of knowledge on the molecular, genetic, and epigenetic aspects of thyroid cancer, research has aimed to specifically profile tumors with more aggressive behavior and/or resistance to therapy [22]. Immune tumor microenvironment [23, 24], epithelial-mesenchymal transition [2528], and some peculiar features including BRAF V600E mutation [29], TERT promoter mutations [30, 31], and transcriptomic signatures [32, 33] have been described as predictors of aggressive DTC. Moreover, several serum or tissue miRNAs (either upregulated or downregulated) have been reported to be involved in DTC initiation, progression, and aggressiveness [34, 35].…”
Section: Discussionmentioning
confidence: 99%